Analysis of Community Satisfaction with Important Performance Analysis on Regional Technical Implementation Unit of Community Health Center - Farradina, Indri; Fahrepi, Reza; Zainal, Henni (Journal of Business Management and Economic Development, 2024)
The aim of the problem in writing this thesis is to determine the suitability between performance and expectations for the services provided by the UPTD Puskesmas Senaken and to find out what attributes are the main priority in improving the quality of service at the UPTD Puskesmas Senaken. The sample in this study was people who visited in June 2023 using an incidental sampling technique, the number of samples obtained was 50 respondents. The community as the research sample was given a questionnaire consisting of 24 statements. The responses to the questionnaire were tested for validity and reliability before the importance performance analysis (IPA) method was carried out using SPSS. The results of testing the research instrument, namely the questionnaire, showed that 24 statement items were declared valid because r count > r table. Apart from that, all statements are reliable because the Cronbach's alpha performance value is > 0.60 (0.916 > 0.60), and Cronbach's alpha expectation > 0.60 (0.916 > 0.60). The value of the level of community satisfaction with the UPTD services at the Senaken Community Health Center is 93%, meaning that the community feels "very satisfied" with the service performance of the UPTD at the Senaken Community Health Center. To improve the quality of UPTD Puskesmas Senaken services more optimally, the UPTD Puskesmas Senaken should immediately improve the attributes, including: officers respond well to the community, officers carry out services appropriately, officers carry out services carefully so that services are fast.